What happened to parents’ views of school success for autistic children during the COVID-19 pandemic? - Cheng, Sheng-Li; Cheng, Sanyin; Liu, Shushan; Li, Yun (Frontiers in Psychiatry, 2023)
Background: The educational views of parents with autistic children directly impacts their children's academic success. However, little research has been done on how the COVID-19 pandemic impacted parents' academic and social views. Aim: This study analyzes parents' views of school success for their autistic children in the context of the COVID-19 pandemic and examines the relationships among pandemic stress, parental involvement, and parents' views of school success for autistic children in mainland China. Methods: In this study, 713 parents of autistic children completed measures assessing their pandemic stress, parental involvement, and views of school success; linear regression and structural equation modeling were used to analyze the data. Result: Parents' views of school success were influenced by factors such as parents' level of education, household income, parents' gender, and children's age. The effects of pandemic stress on views of school success for parents of autistic children are complex: physical and mental reaction has a negative direct effect on views of school success, a positive indirect effect mediated by parental involvement, and a net positive effect; risk perception and concern has a negative indirect effect; and both the direct and indirect effects of pragmatic hopefulness are positive. Education policymakers and practitioners need to seriously and carefully assess these results' implications for modern, inclusive education.